PEMODELAN KARAKTERISTIK PELAKU PERJALANAN TERHADAP PEMILIHAN MODA ANGKUTAN MELALUI TOL PEKANBARU – DUMAI - M Rendy Alfiansyah; Leo Sentosa; Gunawan Wibisono (LPPM Universitas Abdurrab, 2025)
There are differences in the characteristics of travelers on the selection of intercity transportation moda in general at Riau Province and by means of Pekanbaru - Dumai Toll Road. The purpose of this research is to create a model of moda selection characteristics and identify factors that influence the characteristics of travelers on mode choice by means of Pekanbaru - Dumai Toll Road using the Structural Equation Modeling (SEM) method. Data collection is done by distributing questionnaires to respondents. The results of the analysis obtained the highest influence factor on the decision of private transportation travelers affect to public transportation with the model equation PM = 0.276 FL + 0.297 NY + 0.169 BW + 0.154 AM + 0.340 OB is Obstacle, which is still considers using public transportation inefficient, then influenced by convenience, flexibility, time and cost considerations and security while the highest influence factor on the decision of public transport travelers to choose the AKDP Bus or AJDP Travel moda with PM = 0.244 FL + 0.340 B + 0.243 W + 0.228 NY + 0.213 AM model consider of cheaper costs, then flexibility, time considerations, comfort and safety. KeyWords: Mode choice, Structural Equation Modeling (SEM), Pekanbaru - Dumai Toll Road